Binding characteristics and synergistic effects of bacterial expansins on cellulosic and hemicellulosic substrates. (January 2015) - Bunterngsook, Benjarat; Eurwilaichitr, Lily; Thamchaipenet, Arinthip; Champreda, Verawat
Graphical abstract: Highlights: Binding kinetics of five bacterial expansins on polysaccharides was studied. Binding efficiency ( Bmax / Kd ) was in the order of PASC > arabinoxylan > Avicel. All expansins showed varying synergy on hydrolysis of tested substrates. BpEX and CmEX showed the highest synergy of >11-fold on arabinoxylan. Binding and synergy were related to types and crystallinity of substrates. Abstract: Expansins are non-catalytic proteins which loosen plant cell wall structure. In this study, binding kinetics and synergistic action of five bacterial expansins on cellulosic and hemicellulosic polysaccharides were studied. The expansins differed in binding capacity ( Bmax ) and affinity ( Kd ) for different substrates. A common pattern of binding efficiency ( Bmax / Kd ) was found among the expansins tested, in which efficiency was greatest for the phosphoric acid-swollen cellulose (PASC), then the hemicellulose arabinoxylan followed by the microcrystalline cellulose (Avicel PH101). The expansins enhanced the action of Trichoderma reesei cellulase/hemicellulase mixture for degrading all three substrates to varying degrees. Among the substrates and expansins tested, BpEX from Bacillus pumilus and CmEX from Clavibacter michiganensis showed the greatest enhancement effect on arabinoxylan with 11.4 and 12.2-fold greater reducing sugar yield than the reaction with enzyme alone. The work gives insights into the wider application of expansins on enhancing polysaccharide hydrolysis, particularly on hemicellulosic substrates.